Investigating the impact of climatic and environmental factors on HFRS prevalence in Anhui Province, China, using satellite and reanalysis data - Liu, Ying; Liu, Chengyuan; Wang, Liping; Chen, Xian; Qiao, Huijie; Zhang, Yan; Cai, Binggang; Xue, Rongrong; Yi, Chuanxiang (Frontiers in Public Health, 2024)
This study aims to explore the impact of climatic and environmental factors on the Hemorrhagic Fever with Renal Syndrome (HFRS) epidemic in Anhui Province, China, using satellite and reanalysis data. Our findings reveal that HFRS cases predominantly occur during the spring and winter seasons, with the highest peak intensity observed in a 9-year cycle. Notably, the monthly average relative humidity exhibits a Spearman correlation coefficient of 0.404 at a 4-month lag, taking precedence over other contributing factors. Poisson regression analysis elucidates that Normalized Difference Vegetation Index (NDVI) at a 2-month lag, mean temperature (T) and solar radiation (SR) at a 4-month lag, precipitation (P), relative humidity (RH), and aerosol optical depth (AOD) at a 5-month lag exhibit the most robust explanatory power for HFRS occurrence. Moreover, the developed predictive model exhibiting commendable accuracy. Our study provides key evidence for understanding how climatic and environmental factors influence the transmission of HFRS at the provincial scale.